Influence of electron-electron drag on piezoresistance of n-Si - Boiko, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Piezoresistance of n-Si is considered with due regard for inter-valley drag. It has been shown that inter-valley drag gains the piezocoefficient and diminishes the mobility. In the region of nondegenerate carriers, the effect of drag increases when the carrier concentration rises and temperature falls.